Seroprevalence of brucellosis and typing of Brucella melitensis biovar 2 in lactating cows in Kuwait - El-Gohary, Adel; abdelkhalek, Adel; Mohamed, Amro; Al-Sherida, Yousef (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This study was conducted to determine the seroprevalence and typing of brucellosis in lactating cows in some dairy farms in Kuwait. Materials and methods: A total of 4671 serum samples were collected from 4671 apparently healthy lactating cows comprising of 486 from Al-Wafra, 348 from Al-Kabed and 3837 from Al-Salebia areas. The sera were tested by Buffered Acidified Plate Antigen Test (BAPAT), Rose Bengal Plate Test (RBPT) and Complement Fixation Test (CFT) for the presence of brucellosis. Besides, Milk Ring Test (MRT) was done with 60 milk samples collected from 60 lactating cows comprising 18 from Al-Wafra, 5 from Al-Kabed and 37 from Al-Salebia areas. The stomach content of aborted feti were tested for typing of Brucella organism by using specific antisera. Results: The results showed that the overall seroprevalence of bovine brucellosis was 339 (7.25%) by BAPAT, 332 (7.1%) by RBPT, and 329 (7.04%) by CFT. The results revealed that, 42 (8.6%), 5 (1.4%) and 292 (7.6%) sera were positive for brucellosis by BAPAT in the cows of Al-Wafra, Al-Kabed and Al-Salebia areas, respectively. Whereas, their respective number and seroreactive cases by RBPT were 39 (8.02%), 5 (1.4%) and 288 (7.4%). Similarly, as confirmatory test by CFT, the number and seroreactive cases in these areas were 39 (8.02%), 5 (1.4%) and 285 (7.46%). MRT revealed that the average positive case was 61.67% (59.46% in Al-Wafra; 60% in Al-Kabed and 66.6% in Al-Salebia). Two Brucella isolates could be recovered from the stomach content of the two aborted feti and typed as Brucella melitensis biovar 2. Conclusion: Brucellosis is prevalent among lactating cows in Kuwait. This indicates the potential role of these dairy animals in disseminating and spread of such zoonosis to human. Considering public health significance, appropriate preventive measures are suggestive for combating brucellosis in Kuwait. http://doi.org/10.5455/javar.2016.c159